Egy vállalkozás marketingstratégiai-tervének kidolgozása - Varga Roland (2016)
I have chosen this subject, because nowadays in the 21th century the lack of a well made marketing strategy which presents the current market requirements by an enterprise can ca-use the loss of customers and the end of the business. I choose a small local business, Jive-ro Divat, which is one of the best improving local fashion store in town of Lenti. I made a marketing plan which is easily manageable and contains colourful wide range of ideas. The reason of chosen this store is that how i grew up in Lenti. Lenti is a small town in county of Zala and it is close to the Slovenien border. The closeness of the border and the brand new Thermal Hotel Balance give plenty of new op-portunities for the local businesses to improve and to use the classical and modern strategi-es of marketing. The Jivero Divat was founded in 2013. Before this current store, the owner had two smaller ones, but the location was not so attractive like by this one so the owner had decided to closed them and open the Jivero Divat. In order to increase the number of customers we have to find the best method to reach them. Therefore a well made marketingkommunication strategy is essential. Indirect communication happens mainly through Facebook. People use rarely phone or e-mails as a marketingkommunication device. Direct communication mostly happens personally at the moment of selling. Creating a strong relationship among the regular customers is important for the sales manager. The customers can be divided into 3 different groups. First goup is according to the social background we can speak about internal and external buyers. External customers are coming from Slovenia, Austria and Croatia. Internals are mainly the locals and the people who live in the nearby, however because of the newly established hotel, there are more and more buyers from distant towns as well. Secondly we can speak about older and middle-aged people. The number of young customers is not so significant, because the current go-ods doesn't meet their needs at all or just a little bit which is not enogh to make strone rela-tions with them. The third goup is the group of sexes. The Jivero Divat provides clothes for both sex, it can be for a special occasion or just street wears for every days. With the appropriate marketing tools we can reach the young people as well, but on-ly with the proper supply. The store is able to reach excellent results with low input in short-term. The owner should think about the expansion of the store in long-term.